Anesthetic considerations for joint replacement surgery in hemophilic arthropathy: a comprehensive review - H Shafeeq Ahmed; Purva Reddy Jayaram (Anesthesia and Pain Medicine)
Managing hemophilia in patients undergoing joint replacement surgery requires a comprehensive approach encompassing preoperative assessment, meticulous intraoperative care, and tailored postoperative management. Evaluation of joint integrity, bleeding history, and inhibitor presence guides surgical planning and hemostatic therapy selection to optimize outcomes. During surgery, careful attention to factor replacement, antibiotic prophylaxis, anesthetic techniques, and orthopedic strategies minimizes bleeding risk and enhances surgical success. Postoperatively, effective pain management, continued hemostatic therapy, and individualized rehabilitation programs are vital for facilitating recovery and preventing complications. Close monitoring for potential complications, such as periprosthetic joint infection and recurrent hemarthrosis, allows for prompt intervention when necessary. Overall, a collaborative approach involving hematologists, orthopedic surgeons, anesthesiologists, and rehabilitation specialists ensures comprehensive care tailored to the unique needs of patients with hemophilia undergoing joint replacement surgery, ultimately optimizing outcomes and improving quality of life. This holistic approach addresses the multifaceted challenges posed by hemophilia and joint replacement surgery, providing patients with the best possible chance for successful outcomes and long-term joint function. By integrating specialized expertise from multiple disciplines and implementing evidence-based strategies, healthcare providers can effectively manage hemophilia in the context of joint replacement surgery, mitigating risks and maximizing benefits for patients.